Have been informationally efficient stock markets? - Duarte, Juan Benjamín Duarte; Pérez-Iñigo, Juan Manuel Mascareñas (Universidad Pedagógica y Tecnológica de Colombia, 2014)
In this paper we study the testing of the stock market efficiency in the last fifteen years, for that we review the papers of ScienceDirect database to characterize the results in percent. We find that 60 % of papers rejects stock market efficiency, 35 % presents evidence of efficiency, and the remaining 5 % verifies a progressive improvement in efficiency due to economic reforms, faster information flow and the launch of new financial products